Linking attitude and ethical practices to energy efficiency: The mediating role of household lifestyle - Salina, Daud; Wan Noordiana, Wan Hanafi; Sabihah, Hitam; Maryam Jamilah, Asha’ari; Mariam, Abdul Majid; Wan Fadzilah, Wan Yusoff; Maisarah, Ahmad Sofi (Elsevier, 2025)
Several initiatives and policies have been introduced in Malaysia under the National Energy Efficiency Action Plan (NEEAP) 2016–2025 to inculcate a culture of energy-efficient attitudes among households in Malaysia. However, a comprehensive evaluation of the success of the action plan is yet to be reported. Thus, this study has determined the extent to which household attitudes and ethical practices influence the overall effort toward being more efficient in using resources like electricity, with a specific focus on the role played by household lifestyle factors within the state of Selangor, Malaysia. A quantitative research approach using a survey method was adopted to investigate the direct and mediating effects of key variables. Data was contributed by 500 households in Selangor comprising various categories of dwelling. A stratified random sampling was employed to allow for the representativeness of the population. Results from this study indicated that the interactive factors of attitudes, ethical practices, and household lifestyles contributed significantly to energy efficiency usage. Specifically, household attitudes were found to play a pivotal role in shaping energy efficiency outcomes in Selangor. Ethical practices emerged as essential drivers of sustainable energy behaviours, while household lifestyle acted as a mediator between ethical practices and energy efficiency. These findings suggest that energy policies must align closely with underlying social and ethical factors to achieve meaningful change. Through contiguously targeted initiatives led by the state of Selangor to the other states, it is envisaged that the NEEAP 2016–2025 would enable its successful implementation and enhance sustainable household practices in Malaysia.